1995
DOI: 10.1897/1552-8618(1995)14[317:wsccga]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

White Sucker (Catostomus Commersoni) Growth and Sexual Maturation in Pulp Mill-Contaminated and Reference Rivers

Abstract: Induction of hepatic ethoxyresorufin-0-deethylase (EROD) activity and accumulation of chlorophenolic compounds typical of bleached-kraft mill effluent (BKME) in fish sampled downstream of a pulp mill on the St. Maurice River, Quebec, Canada, provided evidence of chemical exposure to BKME. In comparison, fish sampled over the same distances and in similar habitats in a noncontaminated reference river, the Gatineau River, demonstrated low EROD activity and contamination levels. Accelerated growth of white sucker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…This was in agreement with other studies, reporting the role of a BKPME sample, resulting from the use of elemental chlorine in the bleaching process, in the inhibition of reproduction in fish and in GSI reduction Munkittrick et al 1994;Gagnon et al 1995;Denslow et al 2004). According to Sepúlveda et al (2004), other studies have reported that the decrease in gonad size may not always occur after exposures of fish to BKME (McMaster et al 1996a, b).…”
Section: Staining Handesupporting
confidence: 93%
“…This was in agreement with other studies, reporting the role of a BKPME sample, resulting from the use of elemental chlorine in the bleaching process, in the inhibition of reproduction in fish and in GSI reduction Munkittrick et al 1994;Gagnon et al 1995;Denslow et al 2004). According to Sepúlveda et al (2004), other studies have reported that the decrease in gonad size may not always occur after exposures of fish to BKME (McMaster et al 1996a, b).…”
Section: Staining Handesupporting
confidence: 93%
“…The monthly averaged water flow, temperature, and p H for 1990 were 465 k 165 m3/s, 8.3 -1-7.5"C, and 6.7 f 0.3 [25]. At La Tuque, about 1 km upstream from a hydroelectric dam, the river receives the ef-fluent of a pulp mill producing cellate bleached kraft, semibleached-or fully bleached-kraft pulp from black spruce and jackpine [25]. Two bleaching lines are used with the following bleaching sequences: CdNEHD and CdEoDED (Cd, first bleaching stage where chlorine dioxide represents a minor part, N for neutralization, E for extraction with alkali, H for hypochlorite, D for chlorine dioxide, and Eo for caustic extraction with addition of elemental oxygen) [D. Adams, personal communication].…”
Section: Sites Of Studymentioning
confidence: 97%
“…The drainage basin is about half the size of that of the St. Maurice (23,724 km'), and the flow rate is proportionally lower (295 m3/s, monthly average for 1990) making the two rivers hydrodynamically comparable. It is similar in latitude, water pH (6.5 k 0.1, monthly average for 1990), and temperature (8.8 k 8.7"C, monthly average for 1990) to the St. Maurice, and the drainage basin has similar land use (primarily forest) and geology [25]. Furthermore, it has log driving and hydroelectric dams, but no industrial effluent.…”
Section: Gatineau Rivermentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, this same increase was observed, for example, in fish (Catostomus commersoni) living downstream from a pulp and paper mill. These fishes also exhibited several metabolic alterations (including monooxygenase enzyme alterations), delayed age and increased size at maturity, smaller gonads and low fecundity (Hodson et al, 1992;Gagnon et al, 1995).…”
Section: Biological Response and Exposurementioning
confidence: 99%